The Effect of Local Government Strategies on Traditional Market Arrangement in Rengasdengklok District, Karawang Regency - Neri Fajarwati; Roziana Lahmini (Center fo State Civil Apparatus Training and Development and Competency Mapping, 2021)
The government's efforts in structuring traditional markets in Rengasdengklok District, Karawang Regency are deemed ineffective, because the traders leave the building in the market and prefer to sell on the side of the road which causes traffic jams every morning. The government is in the process of constructing a new market building to move traders to a new location. The problem that occurs in the arrangement of this traditional market is the absence of a proper building for traders and traders, which is difficult to arrange properly. As a result, the traders filled the main road of Rengasdengklok and left traces of rubbish on the side of the road. In addition, there is no parking space for buyers. Researchers used the theory of the main components of government strategy (X) from (Mulgan, 2008) which consisted of 5 sub variables, namely purposes, environment, direction, action, and learning. In addition, the researcher uses structuring theory (Y) from (George R Terry, in the book Principles of Management (Sukarna, 2019) which consists of 6 sub variables, namely man, material, machines, method, money, and market. The method used is explanatory. Research with a quantitative approach. Data collection techniques using literature study, questionnaire, observation, and documentation. The population in this study were traders, amounting to 1,314 people. While the sample in this study amounted to 93 people. The sampling method using purposive sampling. Data analysis technique used is the Pearson product moment correlation analysis, hypothesis testing and determinant coefficient. The results showed that the respondents 'responses about the local government strategy were 65.6%, based on the percentage score criteria respondents' answers were categorized as strong. This happens because the government's strategy in conducting market structuring it is good, as for the results in market structuring traditional at 79.0% this is based on the criteria for the respondent's score in the strong category. This is because the market arrangement is good. The influence of local government strategy on traditional market arrangement can be seen that the contribution of influence is 23.8% based on the interpretation guideline of the low coefficient of determination. This happened because there were no proper buildings for traders to sell. Then the remaining 76.2% is influenced by other factors not examined by the researcher.